Growth, survival and morphometrics of intergenerational response to temperature variation in threespine stickleback (Gasterosteus aculeatus) - Helen Spence-Jones; Carla Pein; Lisa N S Shama (PANGAEA, 2024)
Data gathered for a split-clutch experiment on intergenerational response to temperature variation in threespine stickleback (Gasterosteus aculeatus) between May-Nov 2021, at the laboratory in the Wadden Sea Station, Sylt (Germany; 55.020993, 8.437764). Parents were exposed to one of three temperature treatments (constant temperature, natural temperature variation, and increased temperature variation) for 2 months and then bred; clutches were split between the same three temperature treatments and monitored for 90 days post-hatch. Various characteristics were measured to assess the impact and interaction of both parent and offspring temperature variation treatment on offspring growth, survival, and development. Data include standard lengths of parent (n=92) and offspring (n=760) fish (collected using digital measurement of calibrated photographs), timing of breeding events, clutch and egg size, survival of offspring fish over 90 days post-hatch, morphological landmarks for morphometric analysis of offspring fish, and hourly temperatures of treatment conditions.